Impaired proteostatic mechanisms other than decreased protein synthesis limit old skeletal muscle recovery after disuse atrophy - Jordan D. Fuqua; Marcus M. Lawrence; Zachary R. Hettinger; Agnieszka K. Borowik; Parker L. Brecheen; Marcelina M. Szczygiel; Claire B. Abbott; Frederick F. Peelor III; Amy L. Confides; Michael Kinter; Sue C. Bodine; Esther E. Dupont‐Versteegden; et al. (Wiley, 2023)
Abstract Background Skeletal muscle mass and strength diminish during periods of disuse but recover upon return to weight bearing in healthy adults but are incomplete in old muscle. Efforts to improve muscle recovery in older individuals commonly aim at increasing myofibrillar protein synthesis via mammalian target of rapamycin (mTOR) stimulation despite evidence demonstrating that old muscle has chronically elevated levels of mammalian target of rapamycin complex 1 (mTORC1) activity. We hypothesized that protein synthesis is higher in old muscle than adult muscle, which contributes to a proteostatic stress that impairs recovery. Methods We unloaded hindlimbs of adult (10‐month) and old (28‐month) F344BN rats for 14 days to induce atrophy, followed by reloading up to 60 days with deuterium oxide (D2O) labelling to study muscle regrowth and proteostasis. Results We found that old muscle has limited recovery of muscle mass during reloading despite having higher translational capacity and myofibrillar protein synthesis (0.029 k/day ± 0.002 vs. 0.039 k/day ± 0.002, P < 0.0001) than adult muscle. We showed that collagen protein synthesis was not different (0.005 k (1/day) ± 0.0005 vs. 0.004 k (1/day) ± 0.0005, P = 0.15) in old compared to adult, but old muscle had higher collagen concentration (4.5 μg/mg ± 1.2 vs. 9.8 μg/mg ± 0.96, P < 0.01), implying that collagen breakdown was slower in old muscle than adult muscle. This finding was supported by old muscle having more insoluble collagen (4.0 ± 1.1 vs. 9.2 ± 0.9, P < 0.01) and an accumulation of advanced glycation end products (1.0 ± 0.06 vs. 1.5 ± 0.08, P < 0.001) than adult muscle during reloading. Limited recovery of muscle mass during reloading is in part due to higher protein degradation (0.017 1/t ± 0.002 vs. 0.028 1/t ± 0.004, P < 0.05) and/or compromised proteostasis as evidenced by accumulation of ubiquitinated insoluble proteins (1.02 ± 0.06 vs. 1.22 ± 0.06, P < 0.05). Last, we showed that synthesis of individual proteins related to protein folding/refolding, protein degradation and neural‐related biological processes was higher in old muscle during reloading than adult muscle. Conclusions Our data suggest that the failure of old muscle to recover after disuse is not due to limitations in the ability to synthesize myofibrillar proteins but because of other impaired proteostatic mechanisms (e.g., protein folding and degradation). These data provide novel information on individual proteins that accumulate in protein aggregates after disuse and certain biological processes such as protein folding and degradation that likely play a role in impaired recovery. Therefore, interventions to enhance regrowth of old muscle after disuse should be directed towards the identified impaired proteostatic mechanisms and not aimed at increasing protein synthesis.